The Influence of ROA, DER, Total Asset Turnover and Sales Growth on Firm Value (Study of Companies in the Consumption Goods Industrial Sector Listed on The IDX for The 2017-2021 Period) - Indah Rahmawati Rambe; Elwisam Elwisam; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to examine the effect of Return on Assets (ROA), Debt to Equity Ratio (DER), Total Asset Turnover and Sales Growth on Firm Value. The sample of this research is consumer goods industry sector companies listed on the Indonesian stock exchange from 2017-2021 using a purposive sampling method. There are 18 companies in the consumer goods industry sector that meet the criteria to be used as research samples. The analytical method used in this study is multiple linear regression. The dependent variable in this study is company value, measured using price book value (PBV). The results of this study indicate that ROA and Total Asset Turnover have a positive and significant effect on firm value, while DER and Sales Growth have no effect and are not significant on firm value. Simultaneously there is a significant effect on the variables ROA, DER, Total Asset Turnover and Sales Growth on Firm Value.